The Influence of Utilizing Regional Property and Assets Management BLUD Implementation on Regional Genuine Income and Its Implications for Security and Maintenance of Regional Property (Survey on the DKI Jakarta Provincial Asset Management Agency) - Rahmayadi, Ade; Adli Adli (Dinasti International Journal of Digital Business Management, 2023)
The purpose of this research is to analyze and investigate the effect of the Utilization of Regional Property and the Implementation of Asset Management BLUD on Regional Original Revenue and the implications for the Security and Maintenance of Regional Property. The research method used is quantitative, survey, cross-sectional, and confirmative. Data were obtained through a survey by distributing 58 questionnaires to Echelon II, III, and IV officials and functional officials working at the DKI Jakarta Province Regional Asset Management Agency. A total of 55 respondents returned the questionnaire. SEM-PLS was used to analyze data. The study results show that the Utilization of Regional Property and the Implementation of BLUD Asset Management have a significant and positive effect on Regional Original Income; b) The implementation of the Asset Management BLUD has a significant and positive effect on Regional Original Income. Utilization of Regional Property and Implementation of BLUD Asset Management has a significant and positive effect on the Security and Maintenance of Regional Property. Moreover, Regional Original Income significantly and positively affects the Security and Maintenance of Regional Property.